Petrographic characterization of the gold mineralization host rocks of the lavra velha deposit – Ibitiara region, western edge of Chapada Diamantina, Bahia. - Carlin, Aline de Cassia [UNESP]; Zanardo, Antenor [UNESP]; Navarro, Guillermo Rafael Beltran [UNESP] (My University, 2018)
The Lavra Velha gold deposit is located in Ibitiara, Bahia’s central west and the western edge of the physiographic domain of the Chapada Diamantina, situated in Paramirim aulacogen, in northern of São Francisco Craton. The deposit, whose hematite sericitic breccias is hosting the mineralization, was recently insert into the IOCG model class (Iron Oxide Cooper Gold). The main objective of the study was the petrographic characterization of the host rocks of the Lavra Velha deposit, whose predominant lithologies are meta-tonalites and meta-quartz diorite. These rocks are completely altered due to hydrothermal process, which predominates under the deformation at low-strain rate, resulting manly in intense sericitization and iron oxide formation. The petrographic analysis suggests that the deposit’s host rocks correspond to metamorphosed, deformed and hydrothermalized portion of Ibitiara Granitoid. The Ibitiara Granitoid intrusion probably occurs at a shallower crust environment, suggesting that the hydrothermal and mineralizer fluids are later. In spite of the Lavra Velha deposit has being classified as IOCG’s class, the tectonic, structural and hydrothermal analysis suggests that the gold mineralization has originated during Espinhaço basin later deformation stage, related to inversion of the Paramirim aulacogen.
Caracterização petrográfica das rochas encaixantes da mineralização aurífera do depósito lavra velha – Região de Ibitiara, borda oeste da Chapada Diamantina, Bahia.
Keywords: Espinhaço supergroup; IOCG deposits; Lavra velha deposit; Paramirim aulacogen; São francisco craton